THE EVOLUTION OF PAO AN TUI AND ITS ROLE AFTER THE ANTI-CHINESE RACIAL RIOTS IN TANGERANG (1946-1949): Perkembangan Pao An Tui dan Perannya pasca-Kerusuhan Rasial Anti-Tionghoa di Tangerang (1946-1949) - Fani Oktaviani; Sodiq, Ibnu (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to analyze the role of the security forces formed for the Chinese community affected by the anti-Chinese racial riots that occurred in Tangerang in 1946. Using historical research methods that are consist of heuristic, source criticism, interpretation, and historiography, the data used in this research was obtained through analysis of written documents, newspapers, and secondary literature relevant to the research of the evolution of a Chinese security force who is the origins of which can be seen from the anti-Chinese racial riots that happened a year before the forces was officially formed. The findings of this research reveal that the formation of a security force for the Chinese community cannot be separated from the threat in the form of social movements carried out by militia troops due to economic factors. The novelty of this research lies in the analysis of the role of the Pao An Tui Chinese community security group in the anti-Chinese racial riots that occurred in Tangerang in 1946, as well as the evolution of the organization after it was officially formed a year after the riots occurred.